Spectroscopic evidences for the size dependent generation of pd species responsible for the low temperature CO oxidation activity on Pd-SBA-15 nanocatalyst - Soni, Yogita; Pradhan, Sumanta; Bamnia, Mahesh K.; Yadav, A. K.; Jha, S. N.; Bhattacharyya, D.; Khan, Tuhin Suvra; Haider, M. A.; Vinod, C. P. (Applied Catalysis B-Environmental, 2020)
A comprehensive size dependent CO oxidation activity has been demonstrated for Pd-SBA-15 catalysts with Pd NPs of varying sizes such as 1-2, 4-6 and 7-10 nm. Pd-SBA-15 catalyst with smallest sized NPs (Pd-S-N) has been synthesized by modified deposition precipitation method recently developed in our lab. Pd-S-N catalyst (reduced at 400 degrees C) demonstrated CO oxidation activity with lower light off temperature (50 degrees C), clearly one of the best reported for a Pd-silica system. A detailed XPS and in-situ DRIFTS analyses further supported by XAS and DFT calculations reveal the presence of easily decomposable highvalent Pd-oxide on co-ordinatively unsaturated Pd sites (Pdcus). Weak binding of CO on Pdcus sites in small Pd NPs leaving sites for oxygen activation is attributed to the low temperature activity of Pd-S-N for CO oxidation.
Keywords: CO oxidation; high-valent Pd species; Pd nanoparticles; SBA-15; under coordinated Pd atoms